Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/foods9091303
|View full text |Cite
|
Sign up to set email alerts
|

Candelilla Wax Edible Coating with Flourensia cernua Bioactives to Prolong the Quality of Tomato Fruits

Abstract: The improvement of the postharvest quality of tomato fruits was evaluated using an edible coating functionalized with an Flourensia cernua extract evaluating the antifungal, structural, barrier, and optical properties. The formulation and evaluation of an edible coating and its application on tomato was evaluated using a response surface methodology to determine the ideal concentrations of candelilla wax, whey protein, and glycerol. Edible films showed good barrier properties, with water vapor permeability var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 47 publications
2
27
0
1
Order By: Relevance
“…The microbial growth results indicated that the protein hydrolysate-based edible coatings showed significant bioactivity as they inhibited the proliferation of molds and yeasts. Ruiz-Martinez et al [ 75 ] reported the enhancement of the postharvest quality of tomatoes by an edible coating functionalized with a Flourensia cernua extract. Sortino et al [ 76 ] evaluated the effectiveness of an edible coating based on Aloe arborescens and a combined treatment of 1-methylcycyclopropene and edible coating to improve the quality and prolong the shelf life of the “Settembrina” peach.…”
Section: Protection Of Fruits and Vegetables By Appropriate Packaging Methodsmentioning
confidence: 99%
“…The microbial growth results indicated that the protein hydrolysate-based edible coatings showed significant bioactivity as they inhibited the proliferation of molds and yeasts. Ruiz-Martinez et al [ 75 ] reported the enhancement of the postharvest quality of tomatoes by an edible coating functionalized with a Flourensia cernua extract. Sortino et al [ 76 ] evaluated the effectiveness of an edible coating based on Aloe arborescens and a combined treatment of 1-methylcycyclopropene and edible coating to improve the quality and prolong the shelf life of the “Settembrina” peach.…”
Section: Protection Of Fruits and Vegetables By Appropriate Packaging Methodsmentioning
confidence: 99%
“…The application of oils and fats, waxes in coatings, and edible packaging material, to improve the parameters of obtained materials (e.g., reduce water vapor permeability), is an area of interest for numerous studies [ 233 , 234 , 235 , 236 ]. Waxes, characterized by high-molecular masses, are both of plant and animal origin.…”
Section: Conventional Materials Used In the Production Of Dishes And Cutlerymentioning
confidence: 99%
“…Por otro lado, se ha reportado que extractos de las hojas de Flourensia cernua, incorporados a un recubrimiento con base en proteína de suero, glicerol y cera de candelilla forman una barrera protectora, reduciendo la pérdida de peso y firmeza. Además, se observó una mayor vida de anaquel y mejor aspecto visual al final del almacenamiento respecto al control (Ruiz-Martínez et al, 2020). Resultados similares reportaron (Azman, Rostam, Ibrahim & Lob, 2020) quienes observaron pérdida de peso y firmeza en los frutos de jitomate al día 8.…”
Section: Extractos De Plantasunclassified